Herpetic meningomyelitis: An exceptional presentation of herpes simplex virus - Sara Khayer; Imane Sellam; Brahim Abouhali; Mouna ELfane (Radiology Case Reports)
Herpetic meningomyelitis is an inflammation of the meninges and spinal cord caused by Herpes simplex virus type 2 (HSV-2). It typically occurs during HSV-2 reactivation, with or without immunosuppressive factors. We report a rare case of herpetic meningomyelitis in a 41-year-old HIV-positive patient, presenting with rapidly progressive ascending paraparesis. Diagnosis was confirmed by cerebrospinal fluid (CSF) multiplex PCR, revealing HSV-2, and spinal cord MRI showing central hyperintensities. The patient was treated with intravenous acyclovir and corticosteroids, leading to significant neurological recovery. This case highlights the importance of early recognition and management of this rare neurological complication of HSV-2.